Pasteurella multocida Pm0442 Affects Virulence Gene Expression and Targets TLR2 to Induce Inflammatory Responses - He, Fang; Qin, Xiaobin; Xu, Na; Li, Pan; Wu, Xiaoyan; Duan, Lijie; Du, Yiyang; Fang, Rendong; Hardwidge, Philip R.; Li, Nengzhang; Peng, Yuanyi (Frontiers in Microbiology, 2020)
Pasteurella multocida is an important pathogenic bacterium of domestic animals.Here, we found that Pm0442 was dramatically up-regulated in infected mice among 67 predicted lipoproteins of P. multocida serotype A CQ2 strain (PmCQ2), and Pm0442 deletion of PmCQ2 significantly decreased bacterial colonization and inflammatory responses in infectious mice, resulting in improved survival. Meanwhile, PmCQ2Δ0442 could provide 70%-80% protection to mice challenged with 3.08×107 CFU of PmCQ2. Pm0442 participated in the influences of PmCQ2 capsular and lipopolysaccharide (LPS) synthesis and iron uptake-related genes expression affecting the ability of adhesion and anti-phagocytosis. PM0442 bound directly to Toll-like receptor 2 (TLR2) to mediate pro-inflammatory cytokine secretion of IL-1β, TNF-α, IL-6, and IL-12p40 in macrophages via activation of the NF-κB, ERK1/2 and p38 signaling pathways. Our findings demonstrate that PM0442 is a PmCQ2 virulence factor, and provide a new insight into the pathogenesis of P. multocida and the development of new vaccines.